''Even though I work, I am not a whore'': women working in Zanzibar. (1st April 2012) - ,
Abstract : This paper examines the different perceptions of work for women in Zanzibar. Life in Zanzibar is dominated by highly gendered geo-spatial constructs, inextricably linked to private and public space. There are complex and layered perceptions about what is appropriate behaviour for women in public and private, thus work —— particular work in the public space —— is problematic for them. The central hypothesis is that for working women there is a fundamental tension between old and new: between traditional ideas of appropriate behaviour, and notions of modernity; and between what is situated and constructed (locally) as a traditional Zanzibar (''Islamic'') idea of womanhood, and the actual performativity of this, which involves an engagement with modernity. The paper explores the influence of what can loosely be called ''modernity'', and traditional ideas of selfhood. This is set against the backdrop of a society dominated by notions of ''umma'' (''community'' and ''not standing out''), corruption —— on a micro and macro level, and the role of gossip in maintaining the status quo and ''the order of things.'' Part of the ''modernity project'' includes the informalisation of roles (for example as worker and mother), the changing uses and definitions of what is ''public'' and the increasingly fluid definitions of ideas about what constitutes new and old that impinge on this. The paper discusses how women often decide to work ''illegally'' or as an extension of their domestic life (by making food, or running hair salons in their homes, or offering massage) to circumvent the public attention, of work and to disengage with the criticism they face operating in the public space. Whilst a few unusual women work in the public space, and in the public sphere, for all women in Zanzibar, working, whether in public or in private, is a heavily meaning-laden activity; and a problematic site of challenging decisions and re-visioning themselves.